Answer:
Step-by-step explanation:
cant remember what this method is called but
change the second equation to be y = something
x + y = 10
y = -x + 10
plug in this y= in the first equation to get x
4x -2(-x + 10) = 4
4x + 2x -20 = 4
6x = 24
x = 4
then plug in the x we found into the original second equation
4 + y = 10
y = 6
so your ordered pair would be (4,6)
hope this helps <3
Answer:
(x-1)²+ (y-0.5)²=6.25
Step-by-step explanation:
<u>The standard form of equation of a circle is;</u>
(x-a)²+(y-b)²=r² where (a,b) are the center of the circle and r is the radius
<u>Finding the mid-point of the given points</u>
(-1,2) and (3,-1)⇒midpoint will be 1/2(x₁+x₂) , 1/2(y₁+y₂)
midpoint= {1/2(-1+3), 1/2(2+-1)}
midpoint=(1,0.5)
<u>Finding the radius r; the distance from the center to either of the given two points</u>
Apply the distance formula d=√ (x₂-x₁)² +(y₂-y₁)²
Taking (x₁,y₁) as (1,0.5) and (x₂,y₂) as (-1,2) then
d=√ (-1-1)² +(2-0.5)²
d= √ (-2)²+(1.5)²
d=√4+2.25⇒√6.25⇒2.5
r=2.5
<u>Equation of the circle</u>
(x-1)² + (y-0.5)²=2.5²
(x-1)²+ (y-0.5)²=6.25
Answer:
109
Step-by-step explanation:
15+15+15= 45
7+7+7=21
4+4+4=12
4+15×7=109
I hope this helps!
Answer:
180
Step-by-step explanation: